Chemopreventive properties of stilbene derivatives in human breast and prostate cancer cell lines - Sunisa Sangjun; Somsak Ruchirawat; Van Den Berg, Martin; Chongrak Polprasert; Preeda Pakpian; Chulabhorn Research Institute; Mahidol University; Asian Institute of Technology Fellowship; Institute for Risk Assessment Sciences (IRAS), Utrecht University, The Netherlands (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
Thirteen cis-stilbene derivatives (CRI-1 - CRI-13) related to VIOXX®were synthesized and studied for their chemopreventive properties in human breast cancer and prostate cancer cell lines. Based on the different substituents in the stilbene molecule, we established a structure activity relationship (SAR) for cytotoxicity, anti-estrogenicity, cell cycle analysis and apoptosis. The results show that some of these stilbenes have a pronounced effect on these chemopreventive properties. In MCF -7 breast cancer cells, CRI-5, 7, 10, and CRI-12 caused an arrest of the G2/M phase and a reduction of G 1/S phase at various dose levels. CRI -9 only arrest the G 1/S phase in a dose-dependent manner. In addition, some CRr congeners, CRI-6 and 9, have a moderate anti-estrogenic effect. In the LNCaP, prostate cancer cells CRI-5, 7, and 12 arrest the cell cycle in G2/M phase and induced apoptosis. A first SAR for these cis-stilbene derivatives was identified. The presence and position of methoxy and thiomethoxy groups are essential for the tested chemopreventive properties and substitution on the para position of these substituents on the left aromatic ring is a prerequisite. The study shows that some of these synthetic cis-stilbene derivatives have the potential to be chemopreventive agents, as these can effectively interfere with cellular processes those are important for anti-cancer treatment. As these experiments have all been done in tumor cell lines further studies are necessary to identify if these anti-tumor properties can also be found in in vivo situations
A dissertation submitted in partial fulfillment of the requirements for thedegree of Doctor of Technical Science in Environmental Engineering and ManagementInter-University Program on Environmental Toxicology, Technology and Management
Thesis (Ph.D.) - Asian Institute of Technology - Chulabhorn Research Institute - Mahidol University, 2009
Keywords: Stilbene; Cancer cells; Cancer -- Chemoprevention